The art of maternal womb painting: oral history of nurses and midwives - Laia da Mata, Júnia Aparecida; Kakuda Shimo, Antonieta Keiko (Nursing Journal in Costa Rica, 2018)
The present study aimed to describe when, how and why the nurse and the midwife apply the painting on pregnant wombs. It was an exploratory research, qualitative approach, in which thematic oral history was adopted as method. Seven health professionals, who apply painting on the womb and attend pregnant women in Brazil, took part of it. The data provided through interviews conducted between January and May 2016. Data were examined based on the thematic analysis of content, of Laurence Bardin. From the interviews, historical tree of womb painting has been drawn up and three categories emerged, which clarify when, how and why the nurse and the midwife apply this art. The womb painting has been adopted in the prenatal care and in the maternity as a strategy for health education and the promotion of maternal and family well-being.